A Negative Conductivity Material Makes a dc Invisibility Cloak Hide an Object at a Distance. (11th April 2013) - Yang, Fan; Mei, Zhong Lei; Yang, Xin Yu; Jin, Tian Yu; Cui, Tie Jun
Abstract The theoretical design and the first experimental verification of an exterior dc invisibility cloak that can hide an object from dc detection at a distance are presented. Based on the transformation optics theory, the exterior dc cloak requires negative conductivity material to create folded geometry, which will cancel the real geometry of detected object in distance and make it invisible. Negative conductivities are designed and realized using active devices, together with resistor networks, to generate the equivalent conductivity materials required by the exterior dc cloak. An experimental sample of the dc cloak is fabricated on the printed circuit board and the measured result has excellent agreement with numerical and circuit simulations, showing very good cloaking performance at a distance.